ATNA-Journal Of Tourism Studies - Thomas, Joby (Atna Journal of Tourism Studies, 2010)
Volume 5 of "ATNA-Journal of Tourism Studies" contains eight different articles covering various aspects of tourism. The scholarly articles range from wild life tourism, agri-tourism, ecotourism, heritage and sustainable tourism, destination marketing and information technology in tourism. The current issue makes an earnest effort to present varied dimensions of tourism.